Interdecadal to Centennial Climate Variability Surrounding the 8.2 ka Event in North China Revealed Through an Annually Resolved Speleothem Record From Beijing. Issue 1 (9th January 2023) - Duan, Pengzhen; Li, Hanying; Ma, Zhibang; Zhao, Jingyao; Dong, Xiyu; Sinha, Ashish; Hu, Peng; Zhang, Haiwei; Cai, Yanjun; Ning, Youfeng; Edwards, R. Lawrence; Cheng, Hai
Abstract: The 8.2 ka event has been extensively studied, whereas its structure is ambiguous in North China. Here we present a high‐resolution (∼1 year) δ 18 O record from annual laminated speleothem from Beijing to characterize the detailed variability across this event in North China. Our record indicates a dry 8.2 ka event spanning 8.254–8.107 ka BP with a two‐stage structure superimposed by three prominent high δ 18 O excursions. The identical structure of speleothem δ 18 O records between North and central China during the event suggests a common forcing/response in East China, whereas the progressively increased offset between their average values may reflect changes in moisture source or rainout effect. A close comparison with the Greenland ice core records suggests a strong linear response of the Asian summer monsoon to the North Atlantic climate changes across the early and middle stages of the event, but a different mechanism in the termination processes. Plain Language Summary: As the most pronounced abrupt climate event in the Holocene, the 8.2 ka event has been studied using various geological archives worldwide, but its detailed structure in North China and its link to other climate systems remain poorly understood. Since the Beijing speleothem δ 18 O, a proxy of the precipitation δ 18 O, is sensitive to the Asian summer monsoon (ASM) variations, it allows us to establish precise timing and structure of the 8.2 ka event and estimate the cause of it. Our new speleothem δ 18 O record from Beijing reveals a two‐stage structure superimposed by three "V‐shape" excursions during the event and almost exactly covaries with another published speleothem record from central China, suggesting coherent climate changes over the east ASM domain in response to the same forcing. The gradually increased offset between them probably results from the changed atmospheric circulations. Our results suggest a fast climatic signal propagation from the North Atlantic to the ASM domain during the early and middle 8.2 ka event, and another forcing mechanism in the termination processes. Key Points: Annual laminated speleothem δ 18 O record from North China manifests a two‐stage 8.2 ka event superimposed by three positive excursions High consistency in speleothem records from North and central China on interdecadal to multidecadal timescales indicates a common driver The climate forcing for the termination process is different from the early and middle stages of the 8.2 ka event